2013
DOI: 10.1002/hep.26556
|View full text |Cite
|
Sign up to set email alerts
|

Performance of chronic kidney disease epidemiology collaboration creatinine-cystatin C equation for estimating kidney function in cirrhosis

Abstract: Conventional creatinine-based glomerular filtration rate (GFR) equations are insufficiently accurate for estimating GFR in cirrhosis. The Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) recently proposed an equation to estimate GFR in subjects without cirrhosis using both serum creatinine and cystatin C levels. Performance of the new CKD-EPI creatinine-cystatin C equation (2012) was superior to previous creatinine- or cystatin C-based GFR equations. To evaluate the performance of the CKD-EPI creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
126
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(141 citation statements)
references
References 45 publications
10
126
2
3
Order By: Relevance
“…17 Using these equations in children, young adults, the elderly, and people with cirrhosis and HIV also confirmed the high diagnostic performance. [18][19][20][21] With our results, we can probably conclude that the CKD-EPI-creatinine-cystatin C can be used reliably in CGN patients.…”
Section: Discussionsupporting
confidence: 57%
“…17 Using these equations in children, young adults, the elderly, and people with cirrhosis and HIV also confirmed the high diagnostic performance. [18][19][20][21] With our results, we can probably conclude that the CKD-EPI-creatinine-cystatin C can be used reliably in CGN patients.…”
Section: Discussionsupporting
confidence: 57%
“…In a limited number of studies in patients with cirrhosis, the CysC equations tend to show better results than methods based solely on SCr. However, the published performance of the equations is variable, creating uncertainty as to whether these equations may obviate the need for more accurate methods for measuring GFR in cirrhotics (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Recent reports have suggested that serum Cystatin C, which is not influenced by the muscle volume, has been recommended to calculate the eGFR even in LC patients. [26][27][28] Therefore, our data suggest that the use of only serum CA levels cannot precisely estimate secondary CA deficiency status, even in LC patients with mild renal dysfunction.…”
Section: -24mentioning
confidence: 81%